Efektivitas Canva dan Website Flipbook E-Komik Kebakaran Hutan untuk Meningkatkan Membaca Siswa Sekolah Dasar - Anisa Rahmawati; Nurul Istiq’faroh; Muflihatul Qibtiya (CV. Kurnia Grup, 2026)
This study was motivated by the low reading comprehension ability of elementary school students and the limited use of engaging digital learning media, particularly in forest fire mitigation materials. This study aimed to determine the feasibility and effectiveness of using an e-comic entitled “Forest Fire” developed using Canva and presented through a flipbook website to improve fourth-grade students’ reading comprehension skills. This study employed a quantitative approach with a pre-experimental design using a one group pretest–posttest design. The subjects were 15 fourth-grade students of SDN Lidah Kulon IV. Data were collected through tests and interviews and analyzed using the N-gain formula. The results showed that the average pretest score of 12.93 increased to 14.67 in the posttest, with an N-gain value of 0.57, categorized as moderate. This indicates that the use of Canva-based e-comics and flipbooks was moderately effective in improving students’ reading comprehension skills. The media enhanced students’ reading interest, engagement, and understanding through visual and narrative presentation. Therefore, e-comics can serve as an innovative digital learning medium to support literacy development in elementary schools.